Comparative Analysis of the Most Used Versus the Recently Developed Vitiligo Activity and Extent Scores and Their Change With Treatment - Randa Youssef; Nourhan Emad; Rania M Mogawer (Mattioli1885, 2023)
Introduction: There are diverse assessment tools for vitiligo, with no standardized approach that helps unify treatment outcome measures. Thus, comparing different treatment modalities and developing evidence-based recommendations for vitiligo management has been quite challenging. Objectives: We compared the most commonly used tools assessing both vitiligo activity and extent, namely, Vitiligo Disease Activity Score (VIDA) and Vitiligo Area and Severity Index (VASI) score to their newly developed counterparts, namely, Vitiligo Extent Score Plus score (VES plus) and Vitiligo Signs of Activity score (VSAS), to provide insights that would help set recommendations for a unified outcome assessment protocol for vitiligo patients. Methods: Thirty-six active non-segmental vitiligo cases were recruited, 30 of whom  completed 48 sessions of narrow band ultraviolet B (NB-UVB). Patients were assessed for both extent and activity both before and after treatment with NB-UVB. Scores were correlated. Additionally, VES plus was assessed for its reliability in comparison to VASI score. Results: Both extent (VASI and VES plus) and activity scores (VIDA and VSAS) showed significant improvement following treatment. Additionally, VES plus and VASI were positively correlating both before and after treatment as well as their percent change. Furthermore, VES plus proved as reliable as VASI. Regarding activity scores, total, hypochromic and Koebner VSAS only correlated with VIDA following treatment. Confetti VSAS neither correlated with VIDA before nor after treatment. Conclusions: VES plus and VASI scores have proven of comparable reliability. While examination-based VSAS score comes as an additive tool to the history-based VIDA score.